Clinical Outcomes of BCMA CAR-T Cells in a Multiple Myeloma Patient With Central Nervous System Invasion - Wang, Ting; He, Ting; Ma, Lie; Yang, Yazi; Feng, Ru; Ding, Yanping; Shan, Yueming; Bu, Bing; Qi, Feifei; Wu, Fei; Lu, Xin-an; Liu, Hui (Frontiers in Oncology, 2022)
Background: Multiple myeloma (MM) is the second most common hematological malignancy that still lacks effective clinical treatments. In particular, MM with central nervous system (CNS) invasion occurs rarely. Although B cell maturation antigen (BCMA)-targeted chimeric antigen receptor-T (CAR-T) cell therapy has shown great promise for the treatment of relapsed/refractory MM, few studies have reported whether BCMA CAR-T could inhibit MM with CNS invasion. Case presentation: In this study, we report a special case of a 63-year-old male patient, who suffered MM with CNS invasion and presented rapid extramedullary disease (EMD) progression into multiple organs. Before CAR-T cell infusion, this patient received five cycles of bortezomib, adriamycin and dexamethasone (PAD) and an autologous transplant as the front-line treatment, followed by two cycles of bortezomib, lenalidomide, and dexamethasone (VRD) as the second-line regimen and daratumumab, bortezomib, dexamethasone (DVD) as the third-line regimen. Since the patient still showed rapid progressive disease (PD), BCMA CAR-T cells were infused and one month later, a stringent complete response (sCR) was achieved and the response lasted for four months. Meanwhile, only grade 1 cytokine release syndrome (CRS) was observed. Conclusion: This case report demonstrated that BCMA CAR-T could effectively eradicate CNS-involved MM with low adverse events, suggesting that CAR-T cell therapy could be a feasible therapeutic option for this kind of refractory disease. Clinical Trial Registration: ClinicalTrials.gov Identifier: NCT04537442 Keywords: CAR-T, BCMA, multiple myeloma, central nervous system, case report